Designing breathalyser technology for the developing world: how a single breath can fight the double disease burden. (April 2014) - Krisher, Sarah; Riley, Alison; Mehta, Khanjan
Abstract The meteoric rise in the prevalence of non-communicable diseases, alongside already high rates of infectious diseases, is exacerbating the 'double disease burden' in the developing world. There is a desperate need for affordable, accessible and ruggedized diagnostic tools that detect diseases early and direct patients to the correct channels. Breath analysis, the science of utilizing biomarkers in the breath for diagnostic measures, is growing rapidly, especially for use in clinical diagnostic settings. Breathalyser technologies are improving scientifically, but are not yet ready for productization and dissemination to address healthcare challenges. How does one ensure that these new biomedical devices will be suitable for use in developing communities? This article presents a comprehensive review of breath analysis technologies followed by a discussion on how such devices can be designed to conform with WHO's ASSURED criteria so as to reach and sustain in developing countries where they are needed the most.